An investigation of the symptom burden of paediatric cardiology outpatients in Blantyre, Malawi: The patient perspective - Huwa, Cornelius Kondwani (Department of Public Health and Family Medicine, 2018)
Introduction: Children suffering from cardiac disease present with an increasing burden of symptoms throughout the trajectory of their disease. There is little research describing symptom burden among children with cardiac disease in resource-limited settings in general and looking particularly from the patients' perspective. Social, spiritual and psychological symptom burden and challenges are rarely examined in literature. This study was designed to explore the symptom burden of children with cardiac disease by engaging the children in a discussion about their illness with reference to their social (family and school), physical, spiritual and psychological lives. This was done with the understanding that palliative care improves quality of life through alleviation of distressing symptoms. AIM: To determine symptom burden and palliative care needs of paediatric cardiology outpatients from the perspective of the patient. OBJECTIVES: 1. To describe the common physical symptoms of the children coming to cardiology clinic 2. To describe the psychosocial burden of paediatric cardiology patients in outpatient clinic 3. To describe the spiritual symptoms burden of paediatric cardiology patients in outpatient clinic Methods: This was a cross-sectional descriptive study, using qualitative methodology with semi-structured interviews. The study had twelve participants (aged between 8 years and 18 years) and was conducted at Queen Elizabeth Central Hospital (QECH)'s Paediatric Cardiac Clinic. Findings: Pain was a common physical symptom in all the participants. Only 2 participants received analgesia aimed at treating the pain. Other common physical symptoms were breathlessness, fatigue, vomiting and insomnia. Schooling challenges were common with 7 of the participants either repeating a class or starting school at an older age. Availability of a loving and caring family provided an enabling environment. Schools which had been informed of the cardiac condition of the participants were found to be helpful in supporting the children. Faith and religion were found to be important to most of the participants in coping with the disease. Conclusion: Children with cardiac disease have physical, social, psychological and spiritual challenges and symptoms. To alleviate the burden of symptoms, health workers must pay attention and aim to treat all possible reported symptoms and provide support to families. Living with a chronic cardiac condition affects the whole being of a child including relationships, schooling, family and faith.